THE DENGUE FEVER WITH ACUTE RESPIRATORY INFRACTION AND CONJUNCTIVITIS DEXTRA IN 8-YEAR-OLDS: A CASE REPORT - Ayubi, Muhammad Lutfi Al; Binuko, Kautsar Prastudia Eko (Indonesian Journal of Health Science, 2024)
Dengue fever is a disease caused by the dengue virus (DENV-1, DENV-2, DENV-3, and DENV-4) which female Aedes aegypti and Aedes albopictus mosquitoes transmit. There are several cases of DHF in children accompanied by Acuter Respiratory Infection (ARI) and conjunctivitis. This study aims to determine the interaction between the three conditions, which can affect diagnosis and treatment. This research uses a case study method of a boy at RSUD Dr. Harjono S Ponorogo with complaints of fever for 6 days. Fever fluctuates, especially at night and decreases in the morning. There are abnormal laboratory results high in erythrocytes (5.04 Âµl), and low in platelets (136,000 Âµl) on day 6 of fever. The patient in this case was diagnosed with dengue fever with ARI and conjunctivitis dextra and was hospitalized because he could not receive oral medication. No warning signs appeared in the patient, and during hospitalization with fluid, antipyretic and antiemetic treatment, the patient's clinical condition improved, followed by an increase in platelets, and no fever occurred within 2 x 24 hours until the patient returned